(3GdEMUGA GdJQHhjs - (3YeGO(B, (3GdRZhds ((3YeGf(B:s (3OGQ GdTQhb ddfTQ hGdJhRjY(B,s, 2005)
(3jVe GdeaGgje GdCSGSjI dYde GdEMUGA, JfXje GdHjGfGJ hJdNjUgG, ebGjjS GdfRYI GdeQcRjI, ebGjjS GdJTJJ GdJhRjY GdWHjYj hGdYdGeGJ GdeYjGQjI, eYGedGJ GdEQJHGW , GdJhRjY GdYjfj hGdJbOjQ GdEMUGFj , ENJHGQ GdaQVjGJ GdEMUGFjIs
(3GdedGMb U(B.253 (3; GdeQGLY U(B.259s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdWQb GdEMUGFjIs